Claudin-1 Mediated Tight Junction Dysfunction as a Contributor to Atopic March - Xia, Yuhan; Cao, Han; Zheng, Jie; Chen, Lihong (Frontiers in Immunology, 2022)
Atopic march refers to the phenomenon wherein the occurrence of asthma and food allergy tends to increase after atopic dermatitis. The mechanism underlying the progression of allergic inflammation from the skin to gastrointestinal (GI) tract and airways has still remained elusive. Impaired skin barrier was proposed as a risk factor for allergic sensitization. Claudin-1 protein forms tight junctions and is highly expressed in the epithelium of the skin, airways, and GI tract, thus, the downregulation of claudin-1 expression level caused by CLDN-1 gene polymorphism can mediate common dysregulation of epithelial barrier function in these organs, potentially leading to allergic sensitization at various sites. Importantly, in patients with atopic dermatitis, asthma, and food allergy, claudin-1 expression level was significantly downregulated in the skin, bronchial and intestinal epithelium, respectively. Knockdown of claudin-1 expression level in mouse models of atopic dermatitis and allergic asthma exacerbated allergic inflammation, proving that downregulation of claudin-1 expression level contributes to the pathogenesis of allergic diseases. Therefore, we hypothesized that the tight junction dysfunction mediated by downregulation of claudin-1 expression level contributes to atopic march. Further validation with clinical data from patients with atopic march or mouse models of atopic march is needed. If this hypothesis can be fully confirmed, impaired claudin-1 expression level may be a risk factor and likely a diagnostic marker for atopic march. Claudin-1 may serve as a valuable target to slowdown or block the progression of atopic march.